Preparation method and application of atomically dispersed metal nitrogen-carbon composite material

The preparation of atomic-scale dispersed metal nitrogen-carbon composite materials based on support metal oxides solves the problem of difficulty in achieving stable axial coordination in the prior art, and improves its catalytic performance and stability in the field of electrochemistry.

CN115957796BActive Publication Date: 2025-03-14SHANDONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310062919.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-03-14
Estimated Expiration
2043-01-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively realize the preparation of atomic-scale dispersed metal nitrogen carbon materials with stable axial coordination, and are prone to inactivation in the field of electrochemical applications.

Method used

Using a method based on the support metal oxide, the active metal salt and the support metal oxide are fully dissolved and mixed in a formamide solvent, and then reacted in a high-pressure hydrothermal reactor to obtain a precursor, and calcined under the protection of inert gas in a tube furnace to form an atomic dispersed metal nitrogen-carbon composite material with axial coordination.

Benefits of technology

The stable axial coordination structure of atomic-grade dispersed metal nitrogen-carbon composite material is realized, and its catalytic performance and stability in the field of electrochemistry is improved. It is suitable for fuel cells, metal air batteries and electrolytic hydrogen production catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115957796B_ABST
    Figure CN115957796B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing an atomic-level dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide. The formed atomic-level dispersed metal atoms, in addition to the planar nitrogen coordination in the carbon layer, also form an axial oxygen coordination perpendicular to the planar coordination structure with the dangling oxygen on the surface of the carrier metal oxide. The preparation method comprises: adding an active metal salt and a carrier metal oxide to a formamide solvent in a certain proportion, stirring and ultrasonicating until the solution is uniformly dispersed; transferring the precursor solution to a reactor, setting the reaction temperature and duration; washing, centrifuging, and drying the solvent thermal reaction product; placing it in a tubular furnace for high-temperature roasting under the protection of an inert gas; and then obtaining the composite material of the present invention. The present invention has low raw material cost, simple preparation process, and high preparation efficiency. The composite material has excellent electrochemical catalytic activity and stability, and can be applied to fuel cells and metal-air battery cathode oxygen reduction reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of non-precious metal nitrogen-carbon materials, and relates to a preparation method and application of an atomic-level dispersed metal nitrogen-carbon composite material. Background Art

[0002] Atomically dispersed metal nitrogen-carbon materials have attracted extensive attention and research due to their unique electronic structure and excellent catalytic properties, and have shown good application potential in fuel cells, metal-air batteries, water electrolysis, etc. Compared with traditional nanocatalysts, atomically dispersed metal nitrogen-carbon catalytic materials have obvious advantages: ① clear configuration of active sites, ② concentrated configuration of active sites, ③ ultra-high atomic utilization, ④ strong matrix interaction, ⑤ rich quantum effects and size effects, ⑥ using non-precious metals to achieve catalytic activity exceeding that of precious metals.

[0003] At present, its synthesis is mainly achieved by pyrolyzing metal salts and nitrogen-carbon precursors. Many studies have shown that the coordination configuration of atomic-level dispersed metal nitrogen-carbon materials is generally based on three or four coordination in the plane. This is mainly because the planar three or four coordination configuration is relatively stable, which is conducive to the maintenance of the configuration at high temperature and prevents the aggregation of metal components. For example, CN106944119B discloses a method for preparing a carbon nitride-supported single-atom metal catalytic material, which adopts a metal precursor and a carbon nitrogen precursor complexing method, inhibits the agglomeration of metal atoms through the interaction between the metal center and the ligand, and prepares a carbon nitride-supported single-atom metal catalytic material by pyrolyzing the carbon nitrogen precursor and the metal precursor in one step, thereby improving the stability and dispersibility of the single-atom metal catalytic material.

[0004] For most transition metal elements, the planar coordination configuration is not an ideal electroactive configuration. During the catalytic process, atoms easily protrude from the carbon layer, resulting in drastic changes in activity and a significant decrease in stability. In response to this problem, some researchers have proposed changing the coordination mode of the central metal atom by changing the configuration of the ligand. The typical optimized configuration is to introduce additional axial ligands to form a stable coordination configuration, while optimizing the electronic structure, thereby obtaining excellent electrocatalytic performance. However, this type of axial coordination configuration is currently difficult to achieve, and is easily deactivated during high-temperature calcination or catalysis and evolves into a low-activity planar coordination.

[0005] In summary, it is urgent to develop an effective preparation method for atomically dispersed metal nitrogen-carbon materials with stable axial coordination and carry out applied research in the field of electrochemistry. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing an atomic-level dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide.

[0007] The present invention adopts the following technical solution:

[0008] A method for preparing an atomically dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide comprises the following steps:

[0009] Step 1, weighing a certain mass of active metal salt and carrier metal oxide and adding them to a certain volume of formamide solvent in a certain proportion, stirring and ultrasonicating until fully dissolved and mixed to obtain a suspension;

[0010] Step 2, transferring the suspension obtained in step 1 to a high-pressure hydrothermal reactor, and setting a certain reaction temperature and reaction time;

[0011] Step 3, washing, centrifuging and drying the reaction product obtained in step 2 to obtain a precursor;

[0012] Step 4: placing the dried precursor in step 3 in a tubular furnace, and calcining at a certain temperature and time under the protection of an inert gas to obtain an atomically dispersed metal nitrogen-carbon composite material with axial coordination.

[0013] Furthermore, in the method for preparing an atomically dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide, in step 1, the active metal salt is selected from one or more of chlorides, nitrates, acetates, acetylacetonates, and carbonyl salts of metals such as Fe, Co, Ni, Mn, Zn, Mo, Ru, Rh, Pd, Pt, Au, and Ir. The carrier metal oxide is a nano-scale oxide with a stable oxidation state, selected from one or more of the oxides of Ce, Ti, Zr, Nb, Ta, and Al.

[0014] Furthermore, in the method for preparing an atomically dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide, the concentration range of the active metal salt in formamide is: 0.001-0.005 mol L -1 The mass concentration of the carrier metal oxide in formamide is in the range of 0.5-2gL -1 .

[0015] The method for preparing an atomic-level dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide, in step 2, the reaction temperature is 140-220° C., and the reaction time is 6-48 hours.

[0016] Furthermore, the method for preparing an atomically dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide is characterized in that, in step three, the cleaning solution is a mixture of water and ethanol; the speed of the centrifuge is 6000-10000 rpm; and the baking time in the vacuum drying oven is 8-12 hours.

[0017] Furthermore, the method for preparing an atomically dispersed metal nitrogen-carbon composite material with axial coordination based on a carrier metal oxide is characterized in that, in step four, the inert gas is argon or nitrogen; the high-temperature calcination temperature is 600-1100°C, the heating rate is 1-10°C / minute, and the calcination time is 1-10 hours.

[0018] In summary, the advantages and beneficial effects of the present invention are:

[0019] 1. The atomically dispersed metal nitrogen-carbon composite material of the present invention is essentially a single layer of carbon supporting atomically dispersed metal atoms, using nitrogen ligands in the carbon layer to form a planar coordination with the central metal, and using the surface dangling oxygen of the carrier metal oxide to form an axial oxygen coordination perpendicular to the planar coordination structure with the central atom; the obtained composite material has stable physical and chemical properties and good catalytic performance, can be used as a fuel cell, metal-air battery, and water electrolysis hydrogen production catalyst, and has important promotion value.

[0020] 2. The atomically dispersed metal nitrogen-carbon composite material of the present invention is used as an electrocatalyst for oxygen reduction reaction, and the assembled zinc-air battery outputs a higher specific power (209 mW cm -2 ), excellent charge and discharge reversibility and good long-term stability.

[0021] 3. The preparation method of the present invention utilizes the dangling oxygen at the interface of metal oxides, combined with controlled synthesis technology, to coat a single layer of metal nitrogen-carbon material on the surface of the carrier oxide to form a stable axial coordination structure, thereby improving the electrocatalytic activity and stability, and ensuring that in the actual catalytic process, the axial coordination is protected by the carbon layer and is not easily destroyed. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a preparation flow chart of the atomic-level dispersed metal nitrogen-carbon composite material provided by an embodiment of the present invention.

[0023] Figure 2 This is a transmission electron microscope image of the atomic-level dispersed iron-nitrogen-carbon / titanium oxide composite material provided in Example 1 of the present invention.

[0024] Figure 3 This is an element distribution diagram of the atomically dispersed iron-nitrogen-carbon / titanium oxide composite material provided in Example 1 of the present invention.

[0025] Figure 4 This is the XRD spectrum of the atomic-level dispersed iron-nitrogen-carbon / titanium oxide composite material provided in Example 1 of the present invention.

[0026] Figure 5It is the Fe K-edge EXAFS fitting curve of the atomically dispersed iron-nitrogen-carbon / titanium oxide composite material provided in Example 1 of the present invention.

[0027] Figure 6 This is the XRD spectrum of the atomically dispersed cobalt nitrogen carbon / titanium oxide composite material provided in Example 2 of the present invention.

[0028] Figure 7 It is a test curve diagram of the electrochemical oxygen reduction reaction of the atomically dispersed metal nitrogen and carbon / oxide composite material provided by Examples 1-5 of the present invention.

[0029] Figure 8 This is a current-voltage-power test curve of a zinc-air battery of an atomically dispersed metal nitrogen-carbon / oxide composite material provided in Examples 1-2 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] As attached Figure 1 As shown, the typical steps of the method for preparing the atomically dispersed metal nitrogen-carbon composite material provided by the embodiment of the present invention include:

[0032] Step S101, weighing active metal salt and carrier metal oxide, adding them into a certain volume of formamide solvent, stirring and ultrasonicating until fully dissolved and mixed, to obtain a suspension;

[0033] Step S102, transferring the suspension obtained in step S101 to a high-pressure hydrothermal reactor, and setting the reaction temperature and duration;

[0034] Step S103, washing, centrifuging and drying the reaction product obtained in step S102 to obtain a precursor;

[0035] Step S104, placing the precursor dried in step 3 in a tube furnace and calcining it under the protection of an inert gas to obtain an atomically dispersed metal nitrogen-carbon composite material with axial coordination.

[0036] The technical scheme and technical effects of the present invention are further described below in conjunction with specific embodiments.

[0037] Embodiment 1:

[0038] 0.01 mol L -1Add anhydrous ferric chloride and 40 mg of nano-titanium oxide to 40 ml of formamide, combine with sufficient stirring and ultrasound to completely dissolve the ferric chloride in formamide and evenly disperse the nano-titanium oxide in formamide. Move the obtained suspension into a high-temperature reactor and react at 180 degrees Celsius for 12 hours. After the reaction is completed, wash with water and ethanol several times, centrifuge, and vacuum dry at 70°C. After grinding the obtained dry sample in a mortar, place it in a tubular furnace and roast it under nitrogen protection. The roasting temperature is 950 degrees Celsius and the roasting time is 1 hour. The product after roasting is an atomic-level dispersed iron-nitrogen-carbon / titanium oxide composite material.

[0039] See the transmission electron microscope image of the atomically dispersed iron-nitrogen-carbon / titanium oxide composite material for details. Figure 2 The electron microscopy results showed that the prepared atomic-level dispersed iron-nitrogen-carbon / titanium oxide composite material was a single-layer carbon material coated on the surface of nano-scale titanium oxide.

[0040] The transmission electron microscope element distribution photos can be found in Figure 3 , showing that Fe, N, and C elements are mainly distributed on the surface of the composite material, and there is no Fe aggregation, which verifies the high dispersion of Fe and the coating of iron-nitrogen-carbon materials on the titanium oxide surface. Figure 4 The X-ray diffraction spectrum shows that the synthesized Fe-N-C / TiO2 composite material only has diffraction peaks of graphite carbon, titanium oxide and titanium nitride, indicating that there is no aggregation of metal Fe in the material. The extended X-ray absorption fine structure spectrum can be found in Figure 5 , indicating that the intrinsic structure of the active site is a Fe-N4 structure with axial oxygen coordination. The electrochemical catalytic performance results are shown in Figure 7 In alkaline medium, the oxygen reduction performance of the prepared atomically dispersed iron-nitrogen-carbon / titanium oxide composite material was measured to obtain a linear scanning curve with a starting potential of 1.05 V (relative to the standard hydrogen electrode) and a half-wave potential of 0.91 V (relative to the standard hydrogen electrode). Figure 8 The relationship between the voltage and specific power of the zinc-air battery assembled using it and the applied current density shows a high specific power (209mW cm -2 )(209 mW cm -2 The data for the Fe-N-C / TiO composite material is 136.5 mW cm -2 The data is Pt / C).

[0041] Embodiment 2:

[0042] Except that ferric chloride was replaced by 0.01 mol L -1 Anhydrous cobalt chloride is used to prepare an atomic-level dispersed cobalt nitrogen carbon / titanium oxide composite material, and the rest is the same as in Example 1. Figure 6As for its X-ray diffraction spectrum, the synthesized cobalt-nitrogen-carbon / titanium oxide composite material shows only diffraction peaks of graphite carbon and titanium oxide and titanium nitride, indicating that there is no aggregation state of metal Co in the material. Figure 7 This is the linear scanning curve obtained when the prepared atomically dispersed cobalt-nitrogen-carbon material is used as a catalyst for oxygen reduction reaction under alkaline conditions. Figure 8 The relationship between the voltage and specific power of the zinc-air battery assembled for it and the applied current density (174.4mW cm -2 The data for the Fe-N-C / TiO composite material is 136.5 mW cm -2 The data is Pt / C).

[0043] Embodiment 3:

[0044] Except that ferric chloride was replaced by 0.01 mol L -1 Anhydrous manganese chloride was used to prepare an atomic-level dispersed manganese nitrogen carbon / titanium oxide composite material, and the rest was the same as in Example 1.

[0045] Embodiment 4:

[0046] The atomic-level dispersed iron-nitrogen-carbon / zirconium oxide composite material was prepared in the same manner as in Example 1 except that titanium oxide was replaced by zirconium oxide of equal mass.

[0047] Embodiment 5:

[0048] The atomic-level dispersed iron-nitrogen-carbon / cerium oxide composite material was prepared in the same manner as in Example 1 except that titanium oxide was replaced by an equal mass of cerium oxide.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of an atomically dispersed metal nitrogen-carbon composite material with axial coordination in catalyzing oxygen reduction reaction, characterized in that: The preparation method of the composite material comprises: Step 1, weighing a certain mass of active metal salt and carrier metal oxide in a certain proportion, adding them to a certain volume of formamide solvent, stirring and ultrasonicating until fully dissolved and mixed, to obtain a suspension; Step 2, transferring the suspension obtained in step 1 to a high-pressure hydrothermal reactor, and setting a certain reaction temperature and reaction time; Step 3, washing, centrifuging and drying the reaction product obtained in step 2 to obtain a precursor; Step 4, placing the dried precursor in step 3 in a tube furnace, and calcining at a certain temperature and for a certain time under the protection of an inert gas, so as to obtain an atomically dispersed metal nitrogen-carbon composite material with axial coordination; In step 1, the active metal salt is selected from one or more metal salts of Fe, Co, Ni, Mn, Zn, Mo, Ru, Rh, Pd, Pt, Au, and Ir, and the salt is selected from chloride, nitrate, acetate, acetylacetonate, or carbonyl salt; the carrier metal oxide is a nano-scale oxide with a stable oxidation state, selected from one or more oxides of Ce, Ti, Zr, Nb, Ta, and Al; The concentration range of the active metal salt in formamide is: ; The mass concentration range of the carrier metal oxide in formamide is ; In step 2, the reaction temperature is 140-220°C, and the reaction time is 6-48 hours; In step 4, the calcination temperature is 600-1100° C., the heating rate is 1-10° C. / min, and the calcination time is 1-10 hours.

2. The use of an atomically dispersed metal nitrogen-carbon composite material with axial coordination as claimed in claim 1 in catalyzing oxygen reduction reaction, characterized in that: In step 3, the cleaning solution is a mixture of water and ethanol; the rotation speed of the centrifuge is 6000-10000 rpm; and the baking time in the vacuum drying oven is 8-12 hours.

3. The use of an atomically dispersed metal nitrogen-carbon composite material with axial coordination in catalyzing oxygen reduction reaction according to claim 1, characterized in that: In step 4, the inert gas is argon or nitrogen.

Citation Information

Patent Citations

  • A method for preparing carbon nitride-supported single-atom metal catalytic materials

    CN106944119B

  • Support catalyst with active metals in atomic-scale dispersion in carrier as well as preparation method and application of catalyst

    CN110252308A

  • Method for preparing atomic-level dispersed metal nitrogen carbon material based on gas-phase silicon dioxide

    CN110668415A